A Sensitive In vitro Spectrophotometric Hydrogen Peroxide Scavenging Assay using 1,10-Phenanthroline - Mukhopadhyay, Debanjan; Dasgupta, Pinakpani; Roy, Debalina Sinha; Palchoudhuri, Shauroseni; Chatterjee, Ipsita; Ali, Shahnaz; Dastidar, Sujata Ghosh (Free Radicals and Antioxidants)
Introduction: Hydrogen peroxide (H2 O2 ) is a biologically important, non-radical reactive oxygen species (ROS) that can influence several cellular processes. Ability of anti-oxidants to scavenge H2 O2 can be measured by several methods but all the methods are suffering from several lacunae due to poor reproducibility, lack of specificity, inaccuracy, high cost etc. Objective: The present study aimed towards development of a rapid, low cost, reproducible, specific as well as sensitive and accurate method to detect H2 O2 scavenging activity of anti-oxidants. Methods: We have used 1,10-phenanthroline and ferrous ammonium sulphate to detect H2 O2 scavenging activity of anti-oxidants. Results: We revealed that our assay is able to detect the in vitro H2 O2 scavenging activity of both phenolic and non-phenolic anti-oxidants. Furthermore, we found that this assay is highly specific, as scavengers of other types of ROS were unable to show any detectable effect on H2 O2 through this assay. Finally, we tested commercially available non-steroidal anti-inflammatory drugs that are known to possess H2 O2 scavenging activity and in such drugs also we were able to detect their H2 O2 scavenging activity. Conclusion: In conclusion, the proposed spectrophotometric method was rapid, cost effective, reproducible and highly specific to detect in vitro H2 O2 scavenging activity of diverse compounds.
Keywords: Anti-oxidant; H2 O2; Phenolics; Reactive oxygen species; ROS